Crowdfunding Japanese Commercial Animation: Collective Financing Experiences in Anime. Issue 2 (3rd April 2017) - Loriguillo-López, Antonio
ABSTRACT: The current article offers an exploration of the incipient development of crowdfunding anime projects for short and medium-length films. Japanese commercial animation is characterized by the support of a strong production industry that primarily targets local audiences through cross-media projects, developed in synergy with other cultural sectors (such as the publishing industry, record labels, or video game developers). The growing acceptance of anime in markets around the world has strengthened it as one of the most well-known forms of Japanese popular culture and has also resulted in changes to some of the dominant dynamics of its production to adapt to technological innovations. One of these changes has been the rise of crowdfunding, an increasingly popular form of financing involving the patronage of fans from all corners of the world who want to participate in these audiovisual projects. This article analyses the response to some of the more popular initiatives from a historiographical perspective on the production and reception of commercial animation and the main theories related to the relationship between the hyperactive nature of Japanese fandom and collective financing. The conclusions include the confirmation of the increasing receptiveness to anime crowdfunding among potential sponsors—especially among fans based outside Japan on platforms with a global reach, such as Kickstarter—and a consideration of the transformative potential of this phenomenon for a precarious industry and its usefulness as a tool for exploring the viability of the production and distribution of projects by animation studios.